Natriuretic peptides and their usefulness in clinical practise - Aleksandra Skałecka; Karol Krupa; Aleksandra Słabczyńska; Małgorzata Romaniuk; Konrad Suswał; Janusz Milanowski (Kazimierz Wielki University, 2020)
Natriuretic peptides are peptic hormones produced by atrial and ventricular myocytes, and by endothelium of blood vessels, that take part in homeostatic control of water and sodium levels, but also potassium transport, lipolysis in adipocytes and blood pressure regulation.     Three different natriuretic<span class="TextRun SCXW183210463 BCX0" lang="PL"